2010
DOI: 10.1186/1472-6963-10-252
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of chronic diseases and morbidity in primary health care in central Greece: An epidemiological study

Abstract: BackgroundIn Greece there is lack of large epidemiological studies regarding morbidity and mortality in primary health care. The aim of the present study was to estimate the prevalence and morbidity of the most common diseases in a large population sample from primary health care.MethodsFour primary health centres were randomly selected. During one year period, 12 visits were performed in each centre, one per month, in random order and all visitors willing to participate in the study were included. Data on mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
3
7

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 21 publications
6
35
3
7
Order By: Relevance
“…17 Table 1 shows characteristics of those reporting prevalence estimates of 2 or more coexisting chronic conditions. One article reported the prevalence based on 2 or more domains of the Cumulative Illness Rating Scale (CIRS) affected by chronic diseases.…”
Section: Primary Care Settingsmentioning
confidence: 99%
See 2 more Smart Citations
“…17 Table 1 shows characteristics of those reporting prevalence estimates of 2 or more coexisting chronic conditions. One article reported the prevalence based on 2 or more domains of the Cumulative Illness Rating Scale (CIRS) affected by chronic diseases.…”
Section: Primary Care Settingsmentioning
confidence: 99%
“…Three studies sampled patients from those consulting their family physician, 12,13,17 whereas the others included all patients from the selected practices. The number of participants in each study varied tremendously, from 980 to 60,857.…”
Section: Primary Care Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, approaches to achieve the goal of early diagnosis in COPD need a major overhaul, and a culture change is required in primary-care settings. For this reason, a higher index of suspicion, as well as wider use of spirometry for diagnosis, are proposed [33,[38][39][40][41][89][90][91]. A study conducted at the beginning of the economic recession revealed major shortages in rural primary healthcare equipment; only 4.6% of rural doctors had spirometers available for clinical use [91].…”
Section: Secondary Prevention Of Copd In the Years Of Economic Crisismentioning
confidence: 99%
“…Studies focusing on Greek primary healthcare settings reveal that COPD is mainly undiagnosed [33,[38][39][40][41]90]. Ideally, approaches to achieve the goal of early diagnosis in COPD need a major overhaul, and a culture change is required in primary-care settings.…”
Section: Secondary Prevention Of Copd In the Years Of Economic Crisismentioning
confidence: 99%